2020
DOI: 10.1130/b35680.1
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate platform production during the Cretaceous

Abstract: Platform carbonates are among the most voluminous of Cretaceous deposits. The production of carbonate platforms fluctuated through time. Yet, the reasons for these fluctuations are not well understood, and the underlying mechanisms remain largely unconstrained. Here we document the long-term trend in Cretaceous carbonate platform preservation based on a new data compilation and use a climate-carbon cycle model to explore the drivers of carbonate platform production during the Cretaceous. We show that neritic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The early (Aptian–Albian) Cretaceous is regarded as an interval when high rates of volcanic CO 2 in the atmosphere led, via high rates of silicate weathering, to high rates of shallow water carbonate production in the oceans (Pohl et al ., 2020). However, the lakes which produced the BVF and its equivalents were not linked to the Aptian oceans.…”
Section: Discussion: the Bvf Factorymentioning
confidence: 99%
See 1 more Smart Citation
“…The early (Aptian–Albian) Cretaceous is regarded as an interval when high rates of volcanic CO 2 in the atmosphere led, via high rates of silicate weathering, to high rates of shallow water carbonate production in the oceans (Pohl et al ., 2020). However, the lakes which produced the BVF and its equivalents were not linked to the Aptian oceans.…”
Section: Discussion: the Bvf Factorymentioning
confidence: 99%
“…The role of tectonics involves those large‐scale processes affecting rates of continental crustal weathering but also seawater–basalt reactions at spreading ridges, and also serpentinization of exhumed mantle. A view has been reached that atmospheric CO 2 levels are a critical factor in release of the required ions for carbonate accumulation, including high rates of volcanic degassing of CO 2 , which have been proposed as a critical factor in the high neritic carbonate preservation and production rates which characterize the mid‐Cretaceous (Pohl et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2018, 2019) subdivision is a useful addition as it highlights possible diversifications within each factory depending on the dominance of location‐specific environmental factors. Modelling experiments for the Cretaceous (Pohl et al ., 2019, 2020) using the aforementioned subdivision together with a coupled ocean‐atmosphere general circulation model and palaeo‐bathymetry estimates, which were partially based on literature data, produced detailed carbonate factory distribution maps at a global scale for this time period.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid initial subsidence combined with the Hauterivian long‐term sea‐level rise (Haq, 2014) resulted in rapid creation of accommodation facilitating the deposition of transgressive Seismic Unit‐1. The study by Pohl et al (2020; anchored on GTS2012) showed that neritic carbonates production reached the maximum between ca. 120 Ma and 80 Ma preceded by an increase in the production between ca.…”
Section: Discussionmentioning
confidence: 99%
“…100.5 ± 1 Ma between onset and drowning of the carbonate platform. In Section 5.2, the updated age-model is used to compare our record with the Haq (2014) revised eustatic record andPohl et al (2020) carbonate production trends as they are all anchored on the same geologic time scale(Gradstein et al, 2012).…”
mentioning
confidence: 99%